Diários das vidas possíveis: dissidências sexuais e de gênero nos povos do mar - Bezerra, Cleiton da Paz (2021)
Equity in health underscores the ethical-political commitment to the most vulnerable social groups. The peoples of the sea are culturally differentiated by their way of life intertwined with sea fishing and with all its social and symbolic production. Sexual and gender dissidence in this context takes place in the intersectionality of gender- sexuality-ethnicity. The objective was to understand the experiences of sexual and gender dissidents of the peoples of the sea in their intersectionalities and their implications for the promotion of health equity. A critical ethno-research was carried out based on dense descriptions, autobiographical narratives and life stories. A synoptic picture of the sex-gender system of the peoples of the sea was constructed, contemplating the formation and organization of places, the daily negotiations of sexual and gender norms and the singularities of the subjects. An analytical framework was also structured that presents the dimensions of intersectionality on the effects of systems of oppression such as heteronormativity and gender coloniality, including the agencies operated in community life. Sexual and gender expressions in the daily life of sea peoples in their multiple intersections were described. Sexual and gender dissent and its implications on the life and health of dissenting subjects were discussed. It was observed that, in a community of artisanal fishermen, hegemonic masculinity is centered on the fisherman's actions. Differences between men and women were accentuated with the advent of commercial lobster fishing. The concept of generetnicity was coined to refer to the ethnically performed gender. With the deep transformations that take place in these territories, multiple identities, border and mestizos, which intersect each other, are generated. At the same time, heteronormativity gains strength with the strengthening of religious aspects, in a conflict that expands to community spaces. Sad passions consist of social prejudice and happy passions, in the form of art and education, recreate gender and sexuality in other terms. Clues were unveiled for the promotion of sexual health and gender equity in the peoples of the sea who need to deal with strategic identities, rejecting binarisms and essentialisms, seeking intergenerational dialogue and networking, betting on the political capacity to transform the world and build more liveable lives, thus consisting in a critique of culture.